How firms develop resources-capabilities that are in the origin of its competitive advantage over time : case study : José Maria da Fonseca : Vinhos SA - Uva, Rita Maria Sanches de Sousa (2012)
Nowadays, going global is one of the finest solutions to conquer a superior and stable position in such globalized world. When companies are concerned about their businesses and growth, the diversity of geographies becomes an important issue, since it can multiply revenues and create greater brand awareness. Therefore, it is necessary to develop capabilities that allow a company of having sustainable competitive advantage in changing environments. Thus, it is through firm‟s internal organization of its critical resources that companies can gain such advantage. This dissertation aims to analyze how a medium-sized enterprise developed capabilities that underlie its competitive advantage over time. During the analysis, the resource-based view and the dynamic capabilities theories helped addressing the research question, focusing essentially in the internal and external context to the company, respectively. In this case, we tested how José Maria da Fonseca, a Portuguese wine producer, developed its capabilities in order to triumph either at national or international level. This study, not only identifies José Maria da Fonseca‟s strategies on becoming a recognized brand over the years as well as its international-market dependency; but also its capability‟s development which allowed it competing in new markets.